Impact of Dental Trauma on Orthodontic Parameters-A Systematic Review and Meta-Analysis - Mohammad Khursheed Alam; Mohammed Awawdeh; Ali S. Aljhani; Ghada Serhan Alotaib; Huda Abutayyem; Haytham Jamil Alswairki; Mohammad Younis Hajeer (MDPI AG, 2023)
Background and objectives: Investigation into the impact of dental trauma on the results of orthodontic treatment is crucial because it can have a major influence on patient care. However, there has not yet been a thorough review or meta-analysis of the available data, which is inconsistent and scant. Therefore, the goal of this systematic review and meta-analysis is to investigate the impact of dental trauma on orthodontic parameters. Search methods and criterion of selection: Major online databases were searched (beginning from the year 2011) for relevant articles using a properly defined search strategy. Analysis protocol: Risk of bias (RoB) and the Cochrane risk of bias tool were utilized for the purposes of bias evaluation within the individual studies and within the review, respectively. Results: Out of the six clinical trials selected, a significant impact of trauma was observed in individuals in all but one paper. Gender predilection varied across studies and could not be conclusively determined. The follow-up period ranged from two months to two years in the trials. The odds ratio (OR) 0.38 [0.19, 0.77] and the risk ratio (RR) 0.52 [0.32, 0.85] indicated that both the odds as well as the relative risk of experiencing dental trauma were lower in the group with negligible impact compared to the group with noticeable impact. Conclusion and further implications: The findings show that dental trauma significantly affects orthodontic parameters, with lower risk and likelihood of suffering dental trauma in the group with negligible impact than in the group with noticeable impact. However, given the substantial heterogeneity among the studies, it is advised to exercise caution when extrapolating the findings to all populations. Registration and protocol: Registration in the PROSPERO database was carried out before initiating the investigation [CRD42023407218].